2017
DOI: 10.3390/soc7030027
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Taekwondo Training for Undergraduate Students: A Phenomenological Study

Abstract: Abstract:The purpose of this phenomenological research was to discover whether training in the Korean martial art of Taekwondo may benefit undergraduate (UG) students in handling stress. The goal of this innovative approach to learning and stress management was to allow UG students from across disciplines at a metropolitan university achieve an increased sense of emotional balance, inner peace, and overall well-being in body, mind, and spirit. No such study has been conducted before now. This research was mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Participation in routine Taekwondo training can provide adolescents with various physical, mental, and social benefits [ 24 ], and can be beneficial in the stress management of undergraduate students [ 16 ]. In addition, it can be effective in promoting holistic health, by inducing positive changes in body, mind, and spirit [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participation in routine Taekwondo training can provide adolescents with various physical, mental, and social benefits [ 24 ], and can be beneficial in the stress management of undergraduate students [ 16 ]. In addition, it can be effective in promoting holistic health, by inducing positive changes in body, mind, and spirit [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participation in routine Taekwondo training can provide adolescents with various physical, mental, and social benefits [ 24 ], and can be beneficial in the stress management of undergraduate students [ 16 ]. In addition, it can be effective in promoting holistic health, by inducing positive changes in body, mind, and spirit [ 16 ]. Further, Taekwondo has inherent Korean characteristics, such as the specificity of terms and techniques written in Korean, and the norms of etiquettes, reflecting Korean perspectives; thus, it has the ability of providing an experience of the unique culture of Korea [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this theoretical framework, taekwondo (TKD) is a Korean martial art, refined over generations, that engages students in a range of cognitive, physical, emotional, social and educational processes [11,12,13,14,15,16,17,18,19,20]. Recently, TKD has received attention from scholars and researchers, who have investigated the benefits of TKD training among children and adolescents, in terms of cognitive and behavioral improvements [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the results of these studies indicated that athletes practicing taekwondo went through positive psychosocial changes (Duthie, Hope & Barker, 1978, Rothpearl, 1980Nosanchuk, 1981, Nosanchuk & Mac Neil, 1989Skelton et al, 1991;Kurian et al, 1993, Kim, 1995, Kim et al 2011, Tadesse 2016, Benke at al. 2017, Petrovic 2017.…”
Section: Introduce the Problemmentioning
confidence: 99%